2011
DOI: 10.2319/030211-151.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclic loading on the bond strength of metal orthodontic brackets bonded to a porcelain surface using different conditioning protocols

Abstract: Objective: To evaluate cyclic and static shear bond strengths (SSBSs) of metal orthodontic brackets bonded to a porcelain surface using different conditioning protocols. Materials and Methods: A total of 100 feldspathic porcelain disks were fabricated. The specimens were divided into four equal groups. Porcelain surfaces were conditioned with different protocols. In group 1, hydrofluoric acid and Embrace First-Coat primer were used. In group 2, hydrofluoric acid and silane were utilized. In groups 3 and 4, san… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 22 publications
(34 reference statements)
3
20
1
Order By: Relevance
“…Nevertheless this is in accordance with studies by Rahme et al, showing that the marginal fit was similar after using the replica technique and after cementation with glass-ionomer cement [28]. Another study investigating inter alia the marginal fit after using the replica technique compared to cemented samples also showed no significant differences, reporting values of about 100 μm independent of the technique, which is also in accordance with the values of the present study [29]. …”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless this is in accordance with studies by Rahme et al, showing that the marginal fit was similar after using the replica technique and after cementation with glass-ionomer cement [28]. Another study investigating inter alia the marginal fit after using the replica technique compared to cemented samples also showed no significant differences, reporting values of about 100 μm independent of the technique, which is also in accordance with the values of the present study [29]. …”
Section: Discussionsupporting
confidence: 93%
“…The present study shows that sandblasting with silane combination to condition the ceramic surface gives the highest shear bond strength among all the groups which is similar to the results obtained by Abdelnavy YL. 7 The second highest shear bond strength was seen in the group conditioned with hydrofluoric acid and silane combination. This result is concurrent with the results of a study conducted by Schmage P et al 5 Zachrisson Y, Zachrisson B and Buyukyilmaz T 2 had conducted a study, in which he concluded that silane application after sandblasting the ceramic surface significantly increases the bond strength of metal brackets bonded to ceramic surface, which is concurrent to the results obtained in our study.…”
Section: Discussionmentioning
confidence: 94%
“…This finding is concurrent with results from the current study, because thermocycle can decrease the SBS value. However, Abdelnaby 28 reported that 50 lm Al 2 O 3 SB porcelain surface with thermocycling provided a 6.95 MPa SBS value. In the current study, the SBS values of the HF and SB groups showed no significant difference, and similar bond failure modes.…”
Section: Discussionmentioning
confidence: 97%
“…17 Aluminum oxide sandblasting has been widely used to promote micromechanical retention of ceramics (madani 2000). Many studies 27,28 have shown that Al 2 O 3 sandblasting, combined with silane, significantly increased the bond strength of bracket-to-porcelain surface. Girish et al 27 showed that 50 lm Al 2 O 3 SB for 10 sec without thermocycling enhanced to SBS value (15.18 MPa).…”
Section: Discussionmentioning
confidence: 99%